Eight Motivations of High School Students in Memorizing the Qur’an - Putri, Uccy Adeh; Kakoh, Nur Asikin; Anugrah, Muhammad Ichsan; Hanifah, Hanifah (International Journal of Multidisciplinary Research of Higher Education, 2022)
The Qur’an is the source of Islamic religious law. Many people try to memorize the Qur’an to achieve the priority of memorizing the Qur’an. Senior High School is one of the schools that require students to memorize the Qur’an with a target of three chapters of the Qur’an for 3 years. This study aims to analyze the motivation of Senior High School students in memorizing the Qur’an. This study used a qualitative method with a case study approach. Sources of data were taken from five informants through in-depth interviews selected by purposive sampling technique, all informants were students who were participating in the Qur’an memorization program at Senior High School. All interview results were then analyzed thematically and analyzed using the Miles and Huberman pattern. The results showed eight motivations for students in memorizing the Qur’an, the eight motivations were: i) wanting to be loved by Allah SWT, ii) wanting to keep the Qur’an, iii) wanting to always be with the Qur’an, iv) wanting to become a hafiz of the Qur’an, v) wanting to increase the memorization of the Qur’an, vi) want to give glory to both parents, vii) want to give crowns to both parents in the afterlife, viii) encouragement from parents. The results of this study are used as initial data for future researchers in studying this topic with different contexts and issues.